10 advertising principles - Shore, Robert (Vivays Publishing Ltd, 2012)
The popularity of the television series Mad Men has raised the public awareness of advertising firms and what may (or may not) happen behind the scenes. We all recognize advertising when we see it: it's those bits that surround the editorial content in papers and magazines, that interrupt television shows or pop up on the websites you like to browse. Advertising is about creating a message about something and then reaching out to the target audience through various media in the hope that they will react in a particular way -- which in all likelihood means 'buying it.' This book examines the ten key principles underlying all great advertising and shows readers how to create dynamic, well-targeted adverts of their own.